Recent advances in arterial spin labeling MRI for imaging brain tumors - Gabriel Hoffmann; Matthias J. P. van Osch (Magnetic Resonance Materials in Physics, Biology and Medicine, 2026)
Abstract Perfusion MRI plays an important role in brain tumor assessment, especially for tumor grading and differentiation of tumor progression from pseudoprogression. Arterial spin labeling (ASL) MRI is a non-invasive method for measuring cerebral blood flow (CBF) using blood water as an endogenous tracer, which has great clinical potential for brain tumor imaging and might help to lower the use of gadolinium-based contrast agents. In this review, we discuss recent advances of the ASL method with a special focus on brain tumors, including multi-time point ASL which not only allows more accurate CBF quantification, but also yields arterial transit time (ATT) maps. Another method to reduce dependency on ATT is velocity-selective ASL, for which labeling is directly performed in the imaging volume. By performing a physiological challenge, like a hypercapnia breathing challenge, the reactivity of the tumor’s neovasculature can be determined. More recent advances in ASL allow probing the blood–brain barrier (BBB) integrity by measuring the rate of water transport across the BBB (BBB-ASL). By labeling only a single artery, selective ASL sequences can help to identify what part of the tumor is fed by which artery. In conclusion, we see the future potential of ASL MRI not only in replacing contrast agents for perfusion assessment but also in providing additional information to the MRI exam, such as BBB integrity or the architecture of the vascular feeders.